Milkfish Fish as a Business Opportunity Kalirejo Community, Gresik Regency - Rofiqi Rifyal S; Dwi Puji R; Bunga Prastika; Nanda Yuni C; Aris Susanto (Kontribusia : Research Dissemination for Community Development, 2018)
One of the problems experienced by farmers community fish ponds in the village of Kalirejo, Dukun Sub-district, Gresik Regency is the value of the selling price of fish that tend to be cheaper and the lack of information systems in marketing. So far, people only sell milkfish to the local dukun market and lack of innovation done in sales promotion. The community is less fond of milkfish because it has a lot of thorns,but on the side of excess milkfish has many high nutrients, especially omega-3 unsaturated fatty acids and protein content of 20. In connection with this, this activity aims to increase the selling value of milkfish in the market through training activities to pull out the fish's milkfish and diversification products. The method used is training and mentoring activities to pull out the milkfish spines to produce products that have higher selling value, this activity is done by the villagers Kalirejo especially women and housewives, as well as the surrounding community who have the desire to entrepreneurship. The result is a fish without briber can be sold to consumers or processed into new products that are more popular,such as meatballs, nugets, elephant legs and so forth. The conclusion is that unbraced banding fish has a very lucrative business opportunity with the increase of selling price if it can innovate by pulling out milkfish spines and in making a new product, so as to increase the appeal of people to consume milkfish without the need to think about the thorns that exist in the flesh of milkfish, as well as increasing the income of the fish farmers in Kalirejo Village, Dukun Sub-district, Gresik Regency.